2018
DOI: 10.1080/02770903.2018.1474365
|View full text |Cite
|
Sign up to set email alerts
|

Fall episodes in elderly patients with asthma and COPD – A pilot study

Abstract: Elderly asthmatic patients presented a high rate of falls, which is comparable to that of patients with COPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Fall rate was measured as the number of falls self-reported by the participants during the prior year. Falls rate has been previously measured in older adults who suffered from chronic obstructive pulmonary disease and asthma 10.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fall rate was measured as the number of falls self-reported by the participants during the prior year. Falls rate has been previously measured in older adults who suffered from chronic obstructive pulmonary disease and asthma 10.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, respiratory parameters alterations, such as reduced diaphragm contractility, have been related to chronic ankle instability 14. This association may suggest the presence of spirometry alterations 5,6 and high risk of falls 10 in patients with asthma. Consequently, it is plausible the existence of a relationship between respiratory muscles contractibility impairment and ankle instability 14 with reduced foot dorsiflexion range of motion and high risk of falls 11-13.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The increased fall incidence of the chronic kidney disease and hemodialysis population lies in their multiple risk factors including polypharmacy, dementia, diabetic neuropathy, post-hemodialysis postural hypotension, vitamin D deficiency, sarcopenia, and anemia [39,40]. The finding that older asthmatic patients presented a high rate of falls [41] is comparable with that of patients with chronic obstructive pulmonary disorder (COPD) [42] might be related to skeletal muscle dysfunction and cerebral hypoxemia [33]. The escalation of risk of falls among hypertensive patients might result from hypotension induced by stringent control of blood pressure or from early initiation or intensification of antihypertensive therapy [43].…”
Section: Discussionmentioning
confidence: 99%
“…There are other important comorbidities such as frequent falls, which are a problem for elderly patients. Bozek et al [14] found, in patients with asthma and chronic obstructive pulmonary disease (COPD), that the incidence of falls was more prevalent in the COPD group, with 32%, compared with 28% in patients with asthma and patients with polytherapy, depression symptoms, hospitalizations, coronary disease, dementia, and diagnosis of COPD or asthma have a higher risk of falling.…”
Section: Comorbiditiesmentioning
confidence: 99%